THE VOICE OPERATED DRILLING ROBOT (International Journal of Engineering Sciences & Management Research, 2017)
Now a day‟s technology is a part of our day to day life, and even it is used for our personal day to day activities. This technology can be used to eliminate the extra efforts required to complete a task. We use many machines to complete our tasks; some of the machines are involved in our day to life such as fan, washing machines, computers, mobiles, etc. These machines help us to complete our task in an efficient way. Machines are also been used to reduce the efforts involved in constructions of building or infrastructure. One of the machines used is Drilling machine where we used this machine to make hole in a hard solid surface. Usually in home we use drilling machine for making holes in our walls for some reasons. There can be also a situation where we need to use the drilling machine in an unconditional environment or in not suitable environment for human beings. So at these times we need some new advanced technology to control the drilling machine remotely. While we succeed to develop such technology but still it would be complicated to handle or control the machine through remote while we are multitasking. So we are developing a model through which we are eliminating all problems we discussed here.